Study of the plant biodiversity at Najran village, Al-Swayda governorate, Syria (Damascus University Journal of agriculture sciences, 2023)
The research was carried out during the period between December 2020 and June 2021, at Najran village, Al-Swayda, Syria to determine the wild plant species spread in the studied area and their degree of spread, in addition to studying the effect of seed depth in soil on the percentage germination of seeds spotted golden thistle Scolymus maculatus  L. is one of the most common species in the studied area.We had identified 42 plant species belonging to 22 plant families, including ten species of the compound family Asteraceae, and the spread of these species was between medium and common, except for some species that were rare in spread, namely: Yellow Asphodel Asphodeline brevicaulis L., Isatis Isatis lusitanica L.,  Ornithogalum reticulatum Pallas, rock phagnalon Phagnalon rupestre (L.) DC., blackberry nightshade Solanum nigrum L., and Horizontal navelwort Umbilicus horizontalis (Guss.) DC.By comparing the results of this study with the flora of Syria and Lebanon and the available atlases, it was found that there are plant species spread in Najran. However, their spread was mentioned within the Syrian flora in some Syrian governorates, but they were not mentioned in Jabal al-Arab, namely: Scarlet Pimpernel Anagallis arvensis L., Italian bugloss Anchusa italic Mill, madwort Asperugo procumbens L., Iberian star-thistle Centaurea iberica Trevir. & Spreng. goose foots Chenopodium album L., horse weed Conyza ambigua DC., sweet clover Melilotus indicus (L.) All., grape hyacinths Muscari racemosum Mill, narrowleaf plantain Plantago lanceolata L., milk thistle Silybum marianum (L.) Gaertn., Glandular SpeedwellVeronica cymbalaria Bodard. It was also mentioned that the species horizontal navelwort Umbilicus horizontalis spreads in Lebanon only and was not mentioned in  the flora of Syria, in addition to mentioning the spread of the two species Phagnalon rupestre and spotted golden thistle Scolymus maculatus L. in the Syrian flora, The Syrian governorates, including Alswayda, but they were not mentioned in any of the available atlases.The experiment that was carried out in pots on Scolymus maculatus L. seeds showed that the percentage germination of seeds had increased by increasing the depth of seeds.
Keywords: wild plant species; degree of spread; seed depth; average of germination; flora